2022
DOI: 10.1590/1413-812320222710.08822022
|View full text |Cite
|
Sign up to set email alerts
|

Preenchimento do quesito raça/cor na identificação dos pacientes: aspectos da implementação em um hospital universitário

Abstract: Resumo Após 13 anos da publicação da Política Nacional da Saúde Integral da População Negra (PNSIPN), o preenchimento do quesito raça/cor na identificação de pacientes permanece um desafio. Autores têm se debruçado sobre a necessidade de integrar os conhecimentos da ciência da implementação às políticas públicas. O objetivo deste artigo é descrever e analisar a implementação da coleta do quesito raça/cor feito pelos profissionais responsáveis pelo registro dos pacientes num hospital universitário do município … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Isto se deve pela falta de um treinamento que foque nos critérios para o correto preenchimento do quesito raça/cor nos prontuários e nos sistemas de informação da saúde seguindo a Portaria n° 344. Deve-se respeitar o critério de autodeclaração seguindo os padrões do IBGE de cor amarela, branca, preta, parda e indígena 26 .…”
Section: Resultsunclassified
“…Isto se deve pela falta de um treinamento que foque nos critérios para o correto preenchimento do quesito raça/cor nos prontuários e nos sistemas de informação da saúde seguindo a Portaria n° 344. Deve-se respeitar o critério de autodeclaração seguindo os padrões do IBGE de cor amarela, branca, preta, parda e indígena 26 .…”
Section: Resultsunclassified
“…For example, evidence from the US on HealthCare.gov enrollment data showed that non reporters were disproportionately Black or Hispanic [ 40 ]. In Brazil [ 41 ], a study of a university hospital found that 83% of the valid records for race were for White people, 11% for Mixed race, and only 5% for Black individuals. Potential explanations from this study identified a need for more specific training for health professionals for completing the race/color questionnaire, and that staff were afraid of the reaction of patients when asked to self-declare their race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible reasons raised by Oliveira et al [17] was the difficulty in identifying maculopapular rash in people with black skin, but considering that this clinical manifestation primarily occurs mainly in the palmar and plantar regions, generally lighter in black people, this hypothesis still needs proof. Another reason to be considered, already been studied by other authors [18], is related to the completion of race/ color data in health questionnaires, when professionals define the answer to this question by hetero-identification, that is, not considering or not asking for the patient's self-declaration [19], evidencing institutional racism in health services [20].…”
Section: Discussionmentioning
confidence: 99%